Spatiotemporal characteristics and the national variations of borderland use change in Laos within the geopolinomical context - Wang, Yi; Xiao, Chiwei (Frontiers in Forests and Global Change, 2023)
Laos, the only landlocked country in Mainland Southeast Asia (MSEA), has established over 40 geopolinomical mechanisms with its neighboring countries (including China, Vietnam, Cambodia, Thailand, and Myanmar), leading to significant land-use change (LUC) in the border areas. However, the spatial characteristics and national differences of LUC in the border areas of Laos remain unknown. Through the use of land-use products from 1985 to 2020 and by employing GIS spatial analysis, the results indicate that (1) LUC along the Laos border has led to severe and extensive deforestation, primarily attributed to the rapid expansion of construction land and the consistent growth of cropland. (2) With strengthened border cooperation, differences between LUC in Laos and its neighboring countries have decreased since 1985. (3) Cropland and construction land on the Laos–China and Laos–Thailand borders show obvious bordering characteristics, with increasing land-use homogeneity in near-border areas. In contrast, the Laos–Vietnam, Laos–Cambodia, and Laos–Myanmar borders display the opposite trend. (4) Port areas (e.g., Boten–Mohan port) driven by geopolinomical relations have drastic LUC, but they have huge differences. This study provides a database for quantitative research on the interaction between geopolinomical relations and border LUC to promote border geography, including impact and response.